A New RH-Regular Matrix Derived by Jordan's Function and Its Domains on Some Double Sequence Spaces. (19th May 2021) - Erdem, Sezer; Demiriz, Serkan
Abstract : In the present study, we introduce a new RH-regular 4D (4-dimensional) matrix derived by Jordan's function and define double sequence spaces by using domains of 4D Jordan totient matrix J t on some classical double sequence spaces. Also, the α -, β ϑ -, and γ -duals of these spaces are determined. Finally, some classes of 4D matrices on these spaces are characterized.